From personal advice to professional guidance, IDNLearn.com has the answers you seek. Get thorough and trustworthy answers to your queries from our extensive network of knowledgeable professionals.
Sagot :
Certainly! Let's go through each part step by step.
### Part (i): Show that [tex]\((AB)^T = B^T A^T\)[/tex]
1. Define Matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex]:
[tex]\[ A = \begin{bmatrix} 2 & 1 & -1 \\ 1 & -2 & 3 \\ -2 & 1 & 2 \end{bmatrix}, \quad B = \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & 3 \\ 2 & -1 & 1 \end{bmatrix} \][/tex]
2. Calculate the Product [tex]\(AB\)[/tex]:
[tex]\[ AB = \begin{bmatrix} 2 & 1 & -1 \\ 1 & -2 & 3 \\ -2 & 1 & 2 \end{bmatrix} \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & 3 \\ 2 & -1 & 1 \end{bmatrix} = \begin{bmatrix} -2 & -2 & 6 \\ 11 & -7 & -1 \\ 0 & 3 & 1 \end{bmatrix} \][/tex]
3. Calculate the Transpose of [tex]\(AB\)[/tex]:
[tex]\[ (AB)^T = \begin{bmatrix} -2 & 11 & 0 \\ -2 & -7 & 3 \\ 6 & -1 & 1 \end{bmatrix} \][/tex]
4. Calculate the Transpose of [tex]\(B\)[/tex] and [tex]\(A\)[/tex]:
[tex]\[ B^T = \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & -1 \\ 2 & 3 & 1 \end{bmatrix}, \quad A^T = \begin{bmatrix} 2 & 1 & -2 \\ 1 & -2 & 1 \\ -1 & 3 & 2 \end{bmatrix} \][/tex]
5. Calculate the Product [tex]\(B^T A^T\)[/tex]:
[tex]\[ B^T A^T = \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & -1 \\ 2 & 3 & 1 \end{bmatrix} \begin{bmatrix} 2 & 1 & -2 \\ 1 & -2 & 1 \\ -1 & 3 & 2 \end{bmatrix} = \begin{bmatrix} -2 & -2 & 6 \\ 11 & -7 & -1 \\ 0 & 3 & 1 \end{bmatrix} \][/tex]
6. Transpose of [tex]\(B^T A^T\)[/tex]:
[tex]\[ (B^T A^T)^T = \begin{bmatrix} -2 & 11 & 0 \\ -2 & -7 & 3 \\ 6 & -1 & 1 \end{bmatrix} \][/tex]
Clearly,
[tex]\((AB)^T = B^T A^T\)[/tex].
### Part (ii): Show that [tex]\(\text{trace}(AB) = \text{trace}(BA)\)[/tex]
1. Calculate the Product [tex]\(BA\)[/tex]:
[tex]\[ BA = \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & 3 \\ 2 & -1 & 1 \end{bmatrix} \begin{bmatrix} 2 & 1 & -1 \\ 1 & -2 & 3 \\ -2 & 1 & 2 \end{bmatrix} = \begin{bmatrix} -2 & 11 & 0 \\ -2 & -7 & 3 \\ 6 & -1 & 1 \end{bmatrix} \][/tex]
2. Calculate [tex]\(\text{trace}(AB)\)[/tex]:
[tex]\[ \text{trace}(AB) = -2 + (-7) + 1 = -8 \][/tex]
3. Calculate [tex]\(\text{trace}(BA)\)[/tex]:
[tex]\[ \text{trace}(BA) = -2 + (-7) + 1 = -8 \][/tex]
Thus, [tex]\(\text{trace}(AB) = \text{trace}(BA)\)[/tex].
### Conclusion
We have shown that:
1. [tex]\((AB)^T = B^T A^T\)[/tex]
2. [tex]\(\text{trace}(AB) = \text{trace}(BA)\)[/tex]
Both conditions are satisfied for the given matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex].
### Part (i): Show that [tex]\((AB)^T = B^T A^T\)[/tex]
1. Define Matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex]:
[tex]\[ A = \begin{bmatrix} 2 & 1 & -1 \\ 1 & -2 & 3 \\ -2 & 1 & 2 \end{bmatrix}, \quad B = \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & 3 \\ 2 & -1 & 1 \end{bmatrix} \][/tex]
2. Calculate the Product [tex]\(AB\)[/tex]:
[tex]\[ AB = \begin{bmatrix} 2 & 1 & -1 \\ 1 & -2 & 3 \\ -2 & 1 & 2 \end{bmatrix} \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & 3 \\ 2 & -1 & 1 \end{bmatrix} = \begin{bmatrix} -2 & -2 & 6 \\ 11 & -7 & -1 \\ 0 & 3 & 1 \end{bmatrix} \][/tex]
3. Calculate the Transpose of [tex]\(AB\)[/tex]:
[tex]\[ (AB)^T = \begin{bmatrix} -2 & 11 & 0 \\ -2 & -7 & 3 \\ 6 & -1 & 1 \end{bmatrix} \][/tex]
4. Calculate the Transpose of [tex]\(B\)[/tex] and [tex]\(A\)[/tex]:
[tex]\[ B^T = \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & -1 \\ 2 & 3 & 1 \end{bmatrix}, \quad A^T = \begin{bmatrix} 2 & 1 & -2 \\ 1 & -2 & 1 \\ -1 & 3 & 2 \end{bmatrix} \][/tex]
5. Calculate the Product [tex]\(B^T A^T\)[/tex]:
[tex]\[ B^T A^T = \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & -1 \\ 2 & 3 & 1 \end{bmatrix} \begin{bmatrix} 2 & 1 & -2 \\ 1 & -2 & 1 \\ -1 & 3 & 2 \end{bmatrix} = \begin{bmatrix} -2 & -2 & 6 \\ 11 & -7 & -1 \\ 0 & 3 & 1 \end{bmatrix} \][/tex]
6. Transpose of [tex]\(B^T A^T\)[/tex]:
[tex]\[ (B^T A^T)^T = \begin{bmatrix} -2 & 11 & 0 \\ -2 & -7 & 3 \\ 6 & -1 & 1 \end{bmatrix} \][/tex]
Clearly,
[tex]\((AB)^T = B^T A^T\)[/tex].
### Part (ii): Show that [tex]\(\text{trace}(AB) = \text{trace}(BA)\)[/tex]
1. Calculate the Product [tex]\(BA\)[/tex]:
[tex]\[ BA = \begin{bmatrix} 1 & -2 & 2 \\ -2 & 1 & 3 \\ 2 & -1 & 1 \end{bmatrix} \begin{bmatrix} 2 & 1 & -1 \\ 1 & -2 & 3 \\ -2 & 1 & 2 \end{bmatrix} = \begin{bmatrix} -2 & 11 & 0 \\ -2 & -7 & 3 \\ 6 & -1 & 1 \end{bmatrix} \][/tex]
2. Calculate [tex]\(\text{trace}(AB)\)[/tex]:
[tex]\[ \text{trace}(AB) = -2 + (-7) + 1 = -8 \][/tex]
3. Calculate [tex]\(\text{trace}(BA)\)[/tex]:
[tex]\[ \text{trace}(BA) = -2 + (-7) + 1 = -8 \][/tex]
Thus, [tex]\(\text{trace}(AB) = \text{trace}(BA)\)[/tex].
### Conclusion
We have shown that:
1. [tex]\((AB)^T = B^T A^T\)[/tex]
2. [tex]\(\text{trace}(AB) = \text{trace}(BA)\)[/tex]
Both conditions are satisfied for the given matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex].
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Trust IDNLearn.com for all your queries. We appreciate your visit and hope to assist you again soon.